Implementation of Random Oversampling Technique in the K-Nearest Neighbor Method for Creditworthiness Analysis - Ayu Dhita Putri Wulandari; Shantika Martha; Wirda Andani (LPPM Universitas Terbuka, 2024)
Banks are financial institutions, one of whose main activities is providing credit to their customers. The existence of credit granting activities requires the bank to know the feasibility of prospective debtors in receiving credit. Because in practice, credit granting activities still often have bad credit problems. The problem of bad credit can be overcome by analyzing the feasibility of granting credit to prospective debtors. The data used in this study consists of 10 independent variables and 1 dependent variable is collectibility (kol). The collectibility (col) data consists of 500 data for the current debtor class and 26 data for the non-current debtor class, this indicates an imbalance class. So in this study, the application of the random oversampling (ROS) technique is used to overcome the imbalance class with the K-Nearest Neighbor (KNN) method in classifying current and non-current debtor data. ROS was chosen because it can generally provide better results and does not eliminate information from existing data. The analysis results obtained show that the use of the KNN method with the application of ROS is better than the KNN model without ROS, with an accuracy of 84.91% at data testing. The KNN model with ROS can improve the model's ability to classify noncurrent debtor data or the specificity value of the model increases by 25%. In the KNN model without ROS the model cannot classify non-current debtor data correctly at all, this can endanger the bank in making decisions.